The effect of ethnicity in Indonesia on investment experience - Lubis, Khayruna; Damayanti, Sylviana Maya (Journal of Business and Management, 2020)
Abstract. Investors who invest in the stock market are influenced by several factors. Not only because of the stock market performance, but also because of the influence of the psychological and personality characteristics of investors. The purpose of this study is to determine the effect of ethnicity In Indonesia that are Javanese, Sundanese, Tionghua, & Batak on eight characteristics of behavioral biases in investment decision - overconfidence, herding, regret aversion, gambler's fallacy, representativeness, anchoring, cognitive dissonance, and hindsight. In addition to ethnic factors, researchers also added other demographic factors such as monthly income and the type of investment account owned by investors. The questionnaire distributed to undergraduate students who are studying in Bandung and have an investment account. Data collected in this study were 367 respondents. For the analysis method, this research uses logistic regression analysis method. Based on the hypothesis testing of all independent variables, the results show that the difference in ethnicity does not have aninfluence on the behavioral bias in investment decisions.Keywords: Behavioral finance, Behavioral bias, Ethnicity, Cultural, Investment decisions.